2019
DOI: 10.1037/men0000155
|View full text |Cite
|
Sign up to set email alerts
|

The role of masculine norms and gender role conflict on prospective well-being among men.

Abstract: Masculinity has been theorized to be an anxiety-provoking state. Consequently, many researchers have examined masculinity in relation to negative psychological outcomes such as anxiety, depression, and alcohol or substance use. However, emerging research suggests that certain facets of masculinity may also be related to positive psychological outcomes and that there is a need for more empirical research examining the differential impact of distinct masculine norms on both negative and positive outcomes. Accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 37 publications
(53 reference statements)
3
26
0
1
Order By: Relevance
“…On the other hand, men might enjoy masculinity contests. This is because their pursuit of 'success and winning' could boost up their sense of mastery and achievement which in turn yields higher psychological wellbeing [55]. It may be that commenting reflects a genteel variation of this dynamic, with men focusing on other men as the targets most worthy of engagement.…”
Section: Plos Onementioning
confidence: 99%
“…On the other hand, men might enjoy masculinity contests. This is because their pursuit of 'success and winning' could boost up their sense of mastery and achievement which in turn yields higher psychological wellbeing [55]. It may be that commenting reflects a genteel variation of this dynamic, with men focusing on other men as the targets most worthy of engagement.…”
Section: Plos Onementioning
confidence: 99%
“…In this case, society is conceived as a social playing ground in which all actors (male and female) consistently assume a role consciously or unconsciously ( Smith, 2020 ; Yang, 2013 ). The challenge with the role play assumption is that it does not consider behavioural or emotional exhaustion of the actor which in turn leads to role conflict and decreased psychological wellbeing ( Amarachi et al., 2020 ; Kaya et al., 2018 ). Role conflict within this context occurs when work or social role demands are incongruent with the family anticipated role ( Amarachi et al., 2020 ).…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…It is easy to assume that both Physical Prowess and Risk values would be higher for males than for their female counterparts. Accordingly Kaya et al (2019), study longitudinally examined the influence of masculine norms and gender role conflict on eudemonic psychological well-being among young adult college men. Results demonstrated that both masculine norm conformity and gender role conflict were predictive of increased and decreased well-being among young adult men.…”
Section: Discussionmentioning
confidence: 99%